Advocacy For Village Budgeting To Promote Inclusive Development For Women And Children In Cemba Village, Enrekang Regency - Fajar Ladung; Hamsyah Hamsyah (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2025)
This study examines village budget advocacy based on Gender-Responsive Budgeting (GRB) to support inclusive development for women and children in Cemba Village, Enrekang Regency. The predominantly agrarian village faces challenges regarding limited access for women and children to participate in development and the management of village funds, which tends to focus on physical infrastructure. The study employs a qualitative case study approach with key informants from village officials, BPD members, women’s groups, community leaders, and general community members. Data were collected through in-depth interviews, participatory observations, and document studies, then analyzed thematically. Findings indicate major constraints, including limited understanding of GRB principles among village officials and the community, restricted participation of women, and the limited scale of empowerment programs. Nevertheless, GRB implementation enables budget allocations to be more responsive to the needs of vulnerable groups, enhances participation of women and children in development planning, and optimizes local potential through diversified creative enterprises. Monitoring and evaluation serve as essential tools to assess program effectiveness and inform policy improvements. The study contributes academically by expanding literature on village budget advocacy and provides practical recommendations for village governments and policymakers to strengthen equitable, inclusive, and sustainable development. The findings highlight the importance of capacity building for village officials, community training, and multi-stakeholder collaboration for effective GRB implementation.